Variational approach to the asymptotic mean-value property for the p-Laplacian on Carnot groups. (September 2020) - Adamowicz, Tomasz; Kijowski, Antoni; Pinamonti, Andrea; Warhurst, Ben
Abstract: Let 1 ≤ p ≤ ∞ . We provide an asymptotic characterization of continuous viscosity solutions u of the normalized p -Laplacian Δ p G N u = 0 in any Carnot group G .